2021
DOI: 10.3390/su13052996
|View full text |Cite
|
Sign up to set email alerts
|

Palestine Energy Policy for Photovoltaic Generation: Current Status and What Should Be Next?

Abstract: Most of the consumed energy in Palestine comes from Israel. Meanwhile, the Israeli government controls the amount of electricity for Palestinians due to political reasons. This has led to many electricity shortages, prompting the Palestinians to invest in grid connected photovoltaic systems to mitigate electricity shortages. However, the lack of experience and loose energy policies have negatively affected the electricity distribution network in Palestine. Thus, this paper aims to discuss the current energy po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Energy policy is the governmental act implemented by the installers of renewable energy sources, distributors and consumers [19][20][21][22][23]. Energy policies help assist the energy mix in Malaysia and address the barriers and market failures associated with the energy rate [6,24,25].…”
Section: Energy Policies In Malaysiamentioning
confidence: 99%
See 3 more Smart Citations
“…Energy policy is the governmental act implemented by the installers of renewable energy sources, distributors and consumers [19][20][21][22][23]. Energy policies help assist the energy mix in Malaysia and address the barriers and market failures associated with the energy rate [6,24,25].…”
Section: Energy Policies In Malaysiamentioning
confidence: 99%
“…The maximum allowed PV installation capacity is 1000 kW per single account with a maximum of 75% from the maximum demand (MD), i.e., the average of the recorded MD of the past one year or the declared MD for consumers with less than a one-year record. This is applicable for medium-voltage consumers and for low-voltage consumers not exceeding 60% of the fuse rating (for direct meters) or 60% of the current transformer (CT) rating of the metering current transformers [21,25,60].…”
Section: Net Energy Metering 20 (Nem 20)mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies show that user positive experience helps in developing future generation of the technology as well as may increase the usage of technology 7 . In 8 , the researchers found that the solar-powered box-cooker is the best alternative for low-income families in developing countries.…”
Section: Introductionmentioning
confidence: 99%